Effect of coagulants, stage of cream addition and inulin incorporation on the quality characteristics of mascarpone cheese - Zade, sandip Bapu; Ghosh, Bikash C (Indian Journal of Dairy Science, 2018)
ABSTRACTMascarpone cheese is a soft and high-fat Italian cheese which is introduced in Indian market recently. Most of the soft variety cheeses are prepared by acid coagulation. The type of acid influences the yield and texture of cheese whereas some technical variations in manufacturing process and incorporation of food additives affect the quality of cheese. Mascarpone cheese made using lactic acid as coagulant and incorporating cream (50% fat) in two stages (viz., 50% of total fat requirement in milk and rest fat in cheese coagulum) showed maximum yield, minimum fat loss in whey culminating in maximum yield, desired firmness and spreadability as compared to those prepared using citric or acetic acid as coagulants Addition of inulin up to 6% by weight of coagulum in cheese improved the textural characteristics of cheese. Mascarpone cheese made from milk standardized to 5.62 ± 0.19%  fat added with 50% of total fat in the form of 50% fat cream followed by precipitation using lactic acid as a coagulant, and then adding rest of the total fat requirement as well as inulin to the coagulum is recommended.Keywords:  Mascarpone cheese, Acids, Inulin, Rheology, Sensory characteristics.